2006
DOI: 10.1182/blood-2005-08-3249
|View full text |Cite
|
Sign up to set email alerts
|

A nonsense polymorphism in the protein Z-dependent protease inhibitor increases the risk for venous thrombosis

Abstract: The protein Z-dependent protease inhibitor (ZPI) is a hemostatic serpin with anticoagulant activity. As for antithrombin, deficiency of ZPI could have relevant thrombotic consequences. We have studied 6 genetic modifications affecting the ZPI gene, identifying 5 haplotypes. Haplotype H5 is featured by a stop codon at position 67. The relevance of these genetic modifications and haplotypes in venous thrombosis was evaluated in a case-control study including 1018 patients and 1018 age-and sex-matched controls. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
50
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 27 publications
6
50
2
1
Order By: Relevance
“…12 Mice lacking ZPI or PZ developed enhanced thrombosis after arterial injury, 13,14 and the deficiency of ZPI or PZ in humans has been associated with venous thrombosis and peripheral arterial disease. [15][16][17][18] In plasma, PZ circulates as a complex with ZPI. 19 It has been suggested that PZ binds ZPI through its C-terminal protease domain; 11 however, the detailed interactions between PZ and ZPI are unknown, and no structure of either PZ or ZPI is available.…”
Section: Introductionmentioning
confidence: 99%
“…12 Mice lacking ZPI or PZ developed enhanced thrombosis after arterial injury, 13,14 and the deficiency of ZPI or PZ in humans has been associated with venous thrombosis and peripheral arterial disease. [15][16][17][18] In plasma, PZ circulates as a complex with ZPI. 19 It has been suggested that PZ binds ZPI through its C-terminal protease domain; 11 however, the detailed interactions between PZ and ZPI are unknown, and no structure of either PZ or ZPI is available.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these rare variants are also affecting hemostatic factors, such as the A384S in the SERPINC1 gene, 7 the R67X in SERPIN10 gene, 8 or Ser219Gly in the PROCR gene. 9 • In addition, all the protective factors should be incorporated to better estimate the actual individual risk of suffering the disease.…”
Section: Predicting Individual Risk Of Venous Thrombosis ------------mentioning
confidence: 99%
“…7 Interestingly, angiogenesis and immune suppression often go hand-in-hand, sharing similar molecular and cellular mediators. 8 Also in the context of wound healing, immunesuppressive cells would come in handy as safeguards against inappropriate immune reactivity toward endogenous danger signals. Cells such as myeloid-derived suppressor cells (MDSCs), which include a monocytic (MO)-MDSC and a granulocytic polymorphonuclear (PMN)-MDSC fraction, 9 are best known for their ability to suppress the activation of various lymphoid and myeloid cell types, but are also potently pro-angiogenic.…”
mentioning
confidence: 99%
“…The application of various ultrafiltration devices to radiolabeled water, T 3 , and T 4 yielded striking inconsistencies ( Fig. 1, A-D).…”
mentioning
confidence: 99%
“…However, the exact role of ZPI in the coagulation system is still unknown. In a recent study, 1018 patients with an episode of venous thromboembolism and 1018 controls with no history of thromboembolic disease were screened for different ZPI polymorphisms (3 ). A multivariant analysis, which included the Factor V Leiden mutation and the prothombin 20210 GϾA sequence alteration, showed that the R67X change is an independent risk factor for venous thrombosis.…”
mentioning
confidence: 99%